Managing Concussion Patients Via Telehealth Services Compared to In-Person Clinic Visits. Issue 5 (31st May 2022) - Price, August M.; Knell, Gregory; Jones, Carrie; Caze, Todd J.; Abt, John P.; Burkhart, Scott O.
Background: Sports medicine is increasingly relying on telehealth to provide patients with better access to care, timelier visits, and reduced cost. Telehealth technology is a growing modality that needs more research to demonstrate its utility in the clinical management of concussion. Hypothesis/Purpose: The purpose of this study was to compare the total number of visits, days since injury, and recovery time of pediatric concussion patients evaluated via telehealth versus those in-person. We hypothesized that telehealth patients would have fewer total visits, fewer days since injury, and shorter recovery times compared to in-person patients. Methods: Retrospective data from 2019-2021 were abstracted from the medical record for patients aged 4-18 years who were referred to a specialty pediatric concussion clinic. Demographic data included age, sex, and race/ethnicity. Concussion injury and treatment data were examined based on total number of visits, time since injury (days), and recovery time (days). Descriptive statistics were reported as proportions (counts), means (± standard deviations [SD]), and medians (interquartile range [IQR]), as appropriate. The difference between telehealth and in-person treatment data was tested using independent-samples median tests with a significance level set at 0.05. Results: A total of 381 patients were included in the study, 21.5% (82) were managed via telehealth services and 78.5% (299) were seen in-person. Of the telehealth patients, 40.2% (33) were males, 54.9% (45) were non-Hispanic white, and the mean age was 13.95 (±2.99) years. For in-person patients, 52.5% (157) were male, 56.2% (168) were non-Hispanic white, and the mean age was 14.75 (±2.05) years. Telehealth patients were seen a median 4.0 (IQR=2.0-6.0) days since injury and in-person patients were seen a median 3.0 (IQR=2.0-5.0) days since injury ( P =0.98). Telehealth patients' median total visits was 2.0 (IQR=1.0-2.0), while in-person patients was 2.0 (IQR=2.0-3.0) ( P =0.36). Telehealth patients recovered a median 15.0 (IQR=9.0-22.3) days and in-person patients recovered a median of 16.0 (IQR=11-24) days ( P =0.58). Conclusion: In this preliminary study, telehealth and in-person patients did not differ based on concussion treatment and recovery. These findings demonstrate the potential equivalence of pediatric concussion telehealth and in-person treatments; however, future research should examine differences in treatment costs and treatment access (e.g., distance to clinic, insurance types, etc.), while also considering the potential influence of concussion severity on the likelihood to utilize telehealth versus in-person treatment.